Temperature Control Trainer Pada Programmable Logic Controller Omron CJ2H - Fahmi, Mukhamad Awaludin; Harianto, Harianto; Susanto, Pauladie (Journal of Control and Network Systems (JCONES), 2016)
PLC has been much used in industry. With PLC, most production processes can be controlled automatically. This is because PLC always monitor sensors and control actuators. Generally, PLC will work in accordance with program that is uploaded by programmer. PLC that doing the long production activities will have high temperature , the state of high temperature has not been fully recognized if PLC have no temperature sensors. Therefore this research will be built a miniature that have input and output equipment to perform production process in industry. This miniature will use voltage divider to activate several fans according to data acquisition from temperature sensor. The voltage divider determined from several levels based on the level of heat from heater. The last part of this research is displaying the results of temperature sensor on personal computers using CX-Designer. Of the research 6 times, 3 times research heating and 3 times research cooling, there is an average deviation of the setpoint of 0.393666 ºC and average of standart deviation 0.3117ºC.